Serum 4-hydroxynonenal associates with the recurrence of patients with primary cerebral infarction - Liu, Xingliang; Bai, Meiling; Fan, Lei; Lou, Zhan (Frontiers in Cellular Neuroscience, 2022)
Background 4-Hydroxynonenal (4-HNE), an α, β-unsaturated hydroxyalkenal, has been found to be associated with aspirin resistance, which is a risk factor for recurrent cerebral infarction. However, its effect on recurrent cerebral infarction is less defined. We designed this study to investigate the association between 4-HNE and increased risk of recurrent cerebral infarction. Methods We recruited 189 patients with primary cerebral infarction from 2017 to 2019. According to the recurrence of cerebral infarction during the 3-year follow-up period, they were divided into two groups, namely, the non-recurrence group (n = 93) and the recurrence group (n = 96). All patients were analyzed to explore the risk factors for the recurrence of primary cerebral infarction and the predictive value of serum 4-HNE for the recurrence of cerebral infarction. Results The levels of serum 4-HNE in patients of the recurrence group were significantly higher than that in patients of the non-recurrence group. There was a positive correlation between serum 4-HNE levels and the serum levels of triglyceride (r = 0.448, p = 0.008) and low-density lipoprotein cholesterol (LDL-C; r = 0.442, p = 0.002) in primary cerebral infarction patients. Cox proportional hazards modeling showed that demographic and certain clinical parameters, such as age, serum triglyceride levels, the National Institutes of Health Stroke Scale (NIHSS) scores, and serum 4-HNE levels, were independent factors for the recurrence in patients. The results of the receiver operating characteristic (ROC) curve showed that the area under the curve (AUC) value of serum 4-HNE in patients with cerebral infarction recurrence was 0.703, and when the cutoff value of serum 4-HNE was set at 42.34 ng/ml, the sensitivity and specificity values of serum 4-HNE in predicting recurrent cerebral infarction were 79.20 and 52.70%, respectively. Conclusion Serum 4-HNE is an independent risk factor for the recurrence of patients with primary cerebral infarction, and it may become a new intervention way to prevent the recurrence of patients with cerebral infarction.